The Least Developed Countries Report 2020 - United Nations Conference on Trade; Development (United Nations, 2020)
“[This Report] highlights the importance of public investment for LDCs to address their short-term needs. It emphasizes the importance of comprehensive support for meso-level policies for productive capacity development in the context of addressing structural constraints and building the resilience of these countries. The international community should rally to the report’s call for greater solidarity and stronger international support to avert this crisis and build long-term resilience through fostering productive capacities ...” H.E. Dr. Lazarus McCarthy Chakwera, President of the Republic of Malawi